Інтелектуалізація цифрової економіки: економіко-правовий погляд - Бутнік-Сіверський, Олександр Борисович (My University, 2023)
Узагальнено погляди інтелектуалізації цифрової економіки щодо змісту понять «інтелект» та «інтелектуалізація». Розглянуто інтелектуалізацію економіки як передачу функцій праці людини технічним засобам шляхом переходу від аналогового до цифрового методу запису і передачі інформації до комп’ютерної платформи цифровізації, з якою стискається право власності на віртуальні об’єкти. Підтримано використання цифровізації за змістом термінів диджитизація (оцифровування), диджиталізація (цифровізація) та диджитал (цифрова) трансформація як поетапного переходу до цифрового устрою в людино-цифровому середовищі. The author generalized scientific views on the intellectualization of the digital economy from the standpoint of revealing the meaning of «intelligence» and «intellectualization». The intellectualization of the economy is considered as a consecutive stage of the transfer of the fundamental functions of labour from a person to technical means which led to its new quality — digitalization, where it is reproduced the process of transition from analogue to digital method of recording and transmitting information. Such a technical and technological trans- formation contributed to the formation of a digitalization computer platform which repro- duces the process of combining human intellectual resources with information and communi- cation technologies which is a systemic progressive innovative formation with great opportunities, into which computer equipment, technology, telecommunications, and digital software methods of their use are simultaneously developed and combined, as well as which is facing with the problem of ownership of virtual objects and virtual assets, which can certify property rights, in particular the rights of claim to other objects of civil rights. It is noted that the digitalization computer platform in terms of system elements has different rates of development of each of its components in relation to mastering, implementation, and dissemination in the socio-economic and human-digital environment, which requires appropriate coordination. The human-digital environment is a society using digital technologies, where digital rights dominate. From a practical perspective, the principles of the emergence and use of digitization objects are supported in the mean- ing of the terms: digitization, digitalization and digital transformation, depending on the use, role, and participation in digital processes, that allows to justify the sequence of steps in the development of digital economy, at the same time as stages of transition to a digital order in a human-digital environment. Digitization as a process in which a human-digital system is formed, in which the process of transferring information from the source (com- municator) to the recipient is carried out, using the latest digital technologies and digital communication in compliance with digital law.
Keywords: інтелект; інтелектуалізація; цифровізація економіки; компʼютерна платформа інтелектуалізації; віртуальні об’єкти; віртуальні активи; людино-цифрове середовище; людино-цифрова система; intellectualization; intelligence; digitalization of the economy; computer plat- forms of intellectualization; virtual objects virtual assets; human-digital environment; human-digital system